Development of heat-generating polyester fiber harnessing catalytic ceramic powder combined with heat-generating super microorganisms. Issue 11 (July 2014) - Bahng, Gun-Woong; Lee, Jong Doo
One of the major purposes of fiber is to protect the body from hazardous environments and keep the body temperature at its normal level. To enhance thermal insulation, specially processed fibers have been produced to form air pockets, or various types of heat storage materials are mixed with polymer fiber filament yarns. In addition to thermal insulation, heat-generating fibers have recently been developed. In terms of heat-generating mechanism, there are two methods: the chemical method in which heat is generated through reaction with sweat, and physical method, which converts kinetic energy into thermal energy through the continuous expansion and contraction of fibers. Unlike these heat-generating methods, a brand-new fiber that generates heat using microorganisms was developed. Heat-generating polyester yarn was successfully produced by combining heat-generating microorganisms and ceramic powder together. New fabrics made with this yarn showed superior thermal properties compared to other specially developed fabrics for good thermal insulation. In addition to this, since ceramic powder is embedded in yarns, the heat-generating function of fiber was found to operate normally despite tens of washing. This process may open up a new possibility for the development of functional textiles.